Interventions targeting work-related skills in adults with autism spectrum disorders: A comprehensive literature review. - Yarrow, Emily; Tereshko, Lisa M.; Weiss, Mary Jane; Gerhardt, Peter; Magrauth, Megan (Journal of Vocational Rehabilitation, 2024)
Background: Although the population of individuals with autism aging into adulthood continues to rise, the rate of employment remains exceptionally low. While adults with autism spectrum disorder (ASD) experience several social, communicative, or behavioral impairments that hinder their ability to obtain or maintain jobs, several interventions have been helpful in work-related skill acquisition. Objective: This systematic literature review focuses on strategies that improve numerous employment skills for adults diagnosed with ASD. Methods: A systematic literature review using the PRISMA guidelines identified a total of 44 articles that met inclusion criteria to analyze across several dimensions (participant characteristics, skills targeted, measurement systems, settings, interventions, experimental designs, and outcome/maintenance). Results: Many empirical practices were implemented and demonstrated an impact on the development of work-related skills in adults with ASD. Each study demonstrated an increase in work-related skills, with 63.6% of studies reporting changes in performance that were maintained after completion of the intervention, and/or led to paid employment positions at the end of the study. Conclusion: The review clearly indicates that behavior analytic supports in the workplace hold promise to further improve employment and quality of life outcomes for adults with ASD.